Reactivity of Al/CuO nanothermite composites with fluoropolymers - Nie, Hongqi (2021)
Aluminum/copper oxide (Al/CuO) nanothermite is a promising metal fuel due to its high combustion enthalpy and excellent gas-producing characteristics. Fluoropolymers are energetic binders that can potentially be used to make moldable reactive composites without compromising the ignitability of thermites for structural applications. Herein, we report the reactivity of Al/CuO nanothermite composites with two processable fluoropolymers, THV, and Viton. The reactivities of the prepared composites were investigated from pressure measurement. The corresponding reaction mechanism was also studied by post-reaction products analysis. The results showed that both THV and Viton composites, even those containing up to 30 wt.% of fluoropolymer, were ignitable. However, the reactivities of the prepared composites were observed to reduce to different extent depending on the type of fluoropolymers used. The reduced reactivity was ascribed to the subdued nanothermite reaction due to the consumption of copper oxide and aluminum by reacting with the fluoropolymers. Among the two fluoropolymers studied, the THV composite exhibited a relatively higher reactivity. The ignition delay and combustion temperature of the THV composite were further determined.